Changing Balancing Behaviors in Turkish Foreign Policy During AKP Period (2002-2019) - Oktay BİNGÖL (Gazi Akademik Bakış)
States’ foreign policies and their strategies to attain them are not fixed. When international and domestic dynamics change, policies and strategies may change. Although systemic factors play role in this process, government and regime changes come into prominence as principal factors. During the 17-year period of AKP which came to power in 2002, there have been significant changes in the goals and the means of foreign policy. Balancing and balancing behaviors are among important foreign policy implementing means of middle powers like Turkey. In this article, as change process of foreign policy in Turkey is examined, changing balancing behaviors and strategies are emphasized. In this context, states’ balancing behaviors are discussed with a literature review in the first part. In the second part, the question of how a new government restructures a state’s foreign policy is analyzed. In the final part, Turkey’s changing balancing behaviors with regard to the foreign policy restructuring are studied by focusing on the period of 2002-2019.